WORKSHOP UMKM: PEMASARAN BERBASIS LITERASI DIGITAL - Ratri Harida; Cutiana Windri Astuti; Rifa Suci Wulandari; Rizki Mustikasari; lusy novitasari (Diseminasi: Jurnal Pengabdian kepada Masyarakat, 2023)
The Digital Literacy-Based Marketing Workshop for UMKM entrepreneurs in Pomahan Village, Pulung District, Ponorogo Regency, East Java Province is a means to practice photo and video editing skills, and use persuasive language to increase consumer’s interest for UMKM businesses. This activity aimed to make the wider and larger UMKM marketing of the village in the following year. The method of implementing this activity was participatory. The form of activity was counseling and mentoring which was divided into four sessions. The first session was counseling on the benefits of digital marketing for UMKM which included the benefits of digital marketing for UMKM. In the second session, counseling was given regarding the benefits of using persuasive language in marketing to increase the effectiveness and efficiency of UMKM products online marketing. The third session was explanation on the importance of photo and video editing in social media marketing. The fourth session was the practice and mentoring of the use of persuasive language and photo and video editing in social media marketing through Canva and Kinemaster applications. All the sessions provided understanding and experiences for tbe participants to optimize the use of persuasive language and visual elements to increase the effectiveness and efficiency of product marketing. At the end of the activity, the participants gave positive response and actively participated in all the sessions.